Applicability of traditional storage methods in Indonesia for today's conservation practice. (June 2022) - Engel, Patricia
This contribution aims to distil the experience from several conservation projects in Java, Indonesia, into a summary of methods in an attempt to arrive at some suggestions for best practice for the preservation of cultural heritage items in a tropical country. The related projects concerned a museum of contemporary art, traditional puppet theatre materials, a museum of traditional art and an archive.